2008
DOI: 10.1186/1471-2334-8-132
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing and Care in Canadian Aboriginal Youth: A community based mixed methods study

Abstract: Background: HIV infection is a serious concern in the Canadian Aboriginal population, particularly among youth; however, there is limited attention to this issue in research literature. The purpose of this national study was to explore HIV testing and care decisions of Canadian Aboriginal youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 29 publications
1
32
0
3
Order By: Relevance
“…An exploratory mixed-method design was employed, including a cross-sectional survey and in-depth interviews (Mill et al, 2008 (2007), guided the study (Patterson, Jackson, & Edwards, 2006). In order to honor OCAP principles, a community advisory committee (CAC; including Aboriginal youth and Elders) guided the study design, implementation and dissemination of the findings, and a participatory decision-making model was used.…”
Section: Methodsmentioning
confidence: 99%
“…An exploratory mixed-method design was employed, including a cross-sectional survey and in-depth interviews (Mill et al, 2008 (2007), guided the study (Patterson, Jackson, & Edwards, 2006). In order to honor OCAP principles, a community advisory committee (CAC; including Aboriginal youth and Elders) guided the study design, implementation and dissemination of the findings, and a participatory decision-making model was used.…”
Section: Methodsmentioning
confidence: 99%
“…46 Those living on-reserve or in rural areas are less likely to get an HIV test compared to those living in urban settings, 24 which may be due to systemic barriers including concerns about confidentiality and access to testing. 22 Injection drug use is the main exposure category for Aboriginal people infected with HIV. 47 In the three studies included in this review, the highest rates of ever having been tested were among Aboriginal youth who inject drugs (73%), consistent with studies that have shown that individuals who engage in higher-risk activities are also more likely to get tested.…”
Section: Survey Methodsmentioning
confidence: 99%
“…22 Among the total number of Aboriginal youth who injected drugs, 31% had tested at least once a year. 23 Finally, 13.2% of Aboriginal people living off-reserve had an HIV test in the previous year (Table 3).…”
Section: Aboriginal Peoplesmentioning
confidence: 99%
See 2 more Smart Citations